One for All and All for One: Relating team cohesion to the precompetitive emotional response - Wolf, S. A. (Deutsche Sporthochschule Köln, Psychologisches Institut, 2014)
Thesis explains how team cohesion relates to athletes' emotional response to a pending competition. To this end, author conducted two correlational field-studies in which female and male competitive interactive sport athletes completed self-report measures prior to an in- season game. The analyses of these studies demonstrated (a) the relative importance of cohesion (i.e., social Individual Attractions to the Group) to athletes' precompetitive anxiety response when compared to other selected predictors; (b) the initial validity of a novel measure of precompetitive appraisal as the determinant of athletes' precompetitive emotional response; (c) that higher cohesion (i.e., task cohesion and Individual Attractions to the Group) predicted a precompetitive appraisal of higher personal importance of a pending team competition and more positive prospects for coping with competitive demands, respectively; (d) that higher team-identification and greater perceived outcome interdependence mediated the links from cohesion (i.e., task-related Group Integration) to competition importance. The relationships between cohesion and appraisal were the same for all teams, but teams differed in their average competition importance. In sum, my findings indicate that cohesion-building could enhance performance because more positive prospects for coping would entail a more pleasant tone and more facilitative interpretations of precompetitive emotion symptoms and higher competition importance would entail greater motivational force, both of which generally benefit performance. However, coaches and consultants in technically and/or tactically demanding sports should be cautious with regard to cohesion-building because higher competition importance also entails increased emotional intensity, which could harm performance on such tasks.